KINERJA PENDAPATAN DAN BELANJA DAERAH KABUPATEN TULUNGAGUNG SEBELUM, SAAT, DAN PASCA PANDEMI COVID-19 (TAHUN 2017-2022) (Universitas Dian Nuswantoro, 2023)
This study aims to determine the performance of the management of income, expenditure, and financing of the district. Tulungagung 2017-2022. This study uses the analysis variables of the degree of decentralization, the ratio of financial independence, the ratio of expenditure growth, operational expenditure, capital expenditure, and the ratio of direct and indirect expenditure. The results of this study indicate that the analysis of the decentralization of Kab. Tulungagung 2017-2022 is sufficient, the average financial independence ratio is low with a consultative relationship pattern, the average operational expenditure and capital expenditure are good because operational expenditure is less than 90% and capital expenditure is more than 5%, the ratio of direc spending.